Towards regional environmental accounts for Ireland - Commins, Nicola; Crilly, Niamh; Lyons, Sean; Morgenroth, Edgar; TOL, RICHARD S. J. (Statistical and Social Inquiry Society of Ireland, 2009)
Existing environmental accounts for the Republic of Ireland are at the national level. This is fine for continental and global environmental problems, but information at a finer spatial scale is needed for local environmental problems. Furthermore, the impact of environmental policy may differ across space. We therefore construct regional estimates of the environmental pressures posed by Irish households and the environmental problems faced by them. The basic unit of analysis is the electoral district, and the prime data source is the CSO??_??_??_s Small Area Statistics, a product of the Census. We use the results of classifying regressions of the Household Budget Survey to impute domestic energy use. We use engineering relations to impute transport fuel use, and secondary data on household behaviour to impute waste arisings. We use EPA data on drinking water use and quality by county. The results show marked regional differences. Electricity use and waste arisings are higher in the East and in the cities and towns. Transport fuel use is highest in the commuter belts around the cities and towns. Other energy is relatively uniform. There is no clear pattern in estimated drinking water use, which may be due to data quality. Drinking water quality is poor across much of the country, but different counties suffer from different problems. The regional estimates are constructed using data in the public domain. However, various government agencies hold data that would allow for the construction of more detailed, more accurate, and more extensive regional environmental accounts.
read before the Society, March 10th, 2009
Keywords: Regional accounts; Environmental accounts; Energy use; Transport; Household waste; Drinking water quality; Drinking water quantity; 314.15